EFFECT OF HUSBAND SUPPORT ON THE QUALITY LIFE POSPARTUM WOMEN AT WORKING IN THE PUBLIC HEALTH MIRI DISTRICT REGENCY OF SRAGEN - Deny Yuliawan; Faizah Betty Rahayuningsih; Ambarwati - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Puerperium is the period that begins after delivery of the placenta and ends when the contenttools back as pre-pregnancy state which lasts up to 42 days. The purpose of this study was todetermine the effect of husbands' support for the welfare of puerperal women in the Distric tPuskesmas Miri Sragen. This research is a quantitative study with a cross-sectional studydesign, sample size 41 for women. Sampling technique using proportional sampling techniqueusing a large sample formula Lemeshow et al (1997). Research instrument was a questionnaire(Postpartum Social Support Questionnaire (PSSQ)) and Postpartum Quality of Lifequestionnaire (PQOL). Analysis of the data shows the results of Pearson Product MomentPearson correlation test 4 KF husband's support and total support of her husband, with welfare.P<values>0.05 in KF2, KF3, KF4 and total DS with KF means no significant relationshipbetween the respective domains husband support the welfare puerperal women, but nosignificant association between the husband's support on welfare KF1 with puerperal womenwith p=0.004<0.05, the value of the Pearson Product Moment correlation (r) at KF 1 at 0.438**with interpretation/strength interval indicates that the correlation was positive direction ie from0.40 to 0.599. Meanwhile, a positive value indicates the pattern of the relationship betweenhusband and welfare support is unidirectional (the higher the husband's support, the higher theWelfare). In other words, mothers who have high support of her husband will have a goodwelfare (r=0.438**, p<0.05). So Ho is rejected, meaning that there is the influence of husband'ssupport KF 1 on the welfare of puerperal women in the District Puskesmas Miri Sragen.Keywords: Postpartum, Welfare, husband Support